(untitled) (Research, Society and Development, 2023)
The use of technological solutions improves the efficiency and sustainability of agricultores system, such as the use of artificial intelligence (AI), which is an interdisciplinary field that can change the agricultural paradigm to something different from the current one. AI-powered solutions not only allow producers to do more with less, they also improve quality and ensure crops reach market faster. Given the relevance of the topic and the information presented, this integrative literature review aims to address and highlight the importance and possibility of using Artificial Intelligence in Livestock. A bibliographic review was carried out to collect information and data available on the use and application of artificial intelligence in livestock, where the search and compilation of data occurred through the search tools of Google, Google Scholar, SCIELO - Scientific Electronic Library and Ministry of Agriculture, Livestock and Supply. When observing the use of artificial intelligence in livestock, we can infer that its implementation provides the possibility of remote identification and counting of animals, animal behavior and the formation of a database, more precisely, of an individual animal or a property, allowing to the producer and responsible technician to outline strategies that maximize production and reduce costs, in addition to developing a sustainable business.